A Patient on Long-Term Proton Pump Inhibitors Develops Sudden Seizures and Encephalopathy: An Unusual Presentation of Hypomagnesaemia - Nirav Y. Gandhi; Walid K. Sharif; Sumeet Chadha; Jayadave Shakher (Case Reports in Gastrointestinal Medicine)
Objective. To present an unusual but known cause of hypomagnesaemia induced-hypocalcaemia in a chronic GORD patient with severe symptoms with a review of the current literature. Methods. Analysis of the clinical and laboratory findings of the patient and discussion of the multi-factorial nature of his disease and the underlying mechanisms. Results. Our patient described features of magnesium deficiency such as weakness, muscle twitches, and fits with clinical signs of hypocalcaemia: a carpal pedal spasm and paraesthesia. Preadmission blood results revealed low calcium and magnesium levels. He was admitted to ITU, when he presented with seizures and developed encephalopathy. The total vitamin D level was 52.4 nmol/L (>49.9). His U&Es and LFTs were within the normal range with the exception of potassium. He was on Omeprazole for his GORD. With omission of the PPI 1 day after admission and replacement therapy, his ion levels normalised. Conclusion. Hypomagnesaemia is often undiagnosed and is associated with multiple biochemical abnormalities. Treatment focus should be aimed at stopping the PPI and replacing the magnesium. Over use of PPIs is a problem in practice, with the FDA issuing a warning over long-term use. Continued monitoring and decision making on dose reduction/withdrawal is essential to avoid complications.